PERAN SEKOLAH DALAM MENGIDENTIFIKASI GANGGUAN PERKEMBANGAN ANAK DI SD 3 MLATI LOR - Aulia Hapsari Dinar Pramesti; Indah Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The initial steps in identifying developmental problems among elementary school children are an important effort to ensure the availability of educational services that meet students’ needs. This study aims to explore the role of schools, particularly teachers and educational staff at SD 3 Mlati Lor, in identifying and following up on indications of developmental disorders among students in grades I to VI. The study employed a qualitative approach with a case study design. Data were collected through participatory observation of learning activities and student behavior, in-depth interviews with classroom teachers and the principal, and document analysis related to assessments and students’ developmental records. The results indicate that the school plays an active role in observing students’ learning behaviors and social interactions, utilizing learning assessments as a basis for early identification, and establishing communication with parents as a form of collaboration to support children’s development. However, the identification process still faces challenges, including limited availability of standardized screening instruments, variations in teachers’ understanding of the characteristics of developmental disorders, and limited access to professional personnel for further diagnosis. These findings highlight the importance of strengthening teachers’ capacity, developing a more structured assessment system, and reinforcing school policies based on inclusive education and the Merdeka Curriculum so that educational services can be more responsive to children’s developmental needs.